2016
DOI: 10.1116/1.4954390
|View full text |Cite
|
Sign up to set email alerts
|

Samarium electrodeposited acetate and oxide thin films on stainless steel substrate characterized by XPS

Abstract: Characterization of a samarium thin film deposited on a stainless steel substrate using electrodeposition was carried out with a Thermo Scientific K-Alpha X-ray photoelectron spectrometer. Two types of samarium electrodeposition samples were studied, one as-deposited and one heated to 700 °C in an air atmosphere. Survey scans include peaks coming from the stainless steel substrate, such as Fe and Cr. An x-ray photoelectron spectroscopy (XPS) survey spectrum, Sm 3d, C 1s, and O 1s narrow scans are shown. It was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 10 publications
0
5
0
Order By: Relevance
“…In brief, with more details contained in [9], the REDC at ORNL has continued [27][28][29][30] to provide unique capabilities for the production of target material intended for use in studies of superheavy element synthesis. It was recognized that aged californium sources, in some cases more than 40 years, would provide a good source of target material for superheavy element (SHE) experiments due to its relative enrichment of isotopes with longer halflives than that of 252 Cf.…”
Section: Mixed-cf Targetmentioning
confidence: 99%
“…In brief, with more details contained in [9], the REDC at ORNL has continued [27][28][29][30] to provide unique capabilities for the production of target material intended for use in studies of superheavy element synthesis. It was recognized that aged californium sources, in some cases more than 40 years, would provide a good source of target material for superheavy element (SHE) experiments due to its relative enrichment of isotopes with longer halflives than that of 252 Cf.…”
Section: Mixed-cf Targetmentioning
confidence: 99%
“…It is evident from the UPS spectra in Figure 1b that the valance band edge is 4.80 ± 0.05 eV below the Fermi level ( E f ) and addition of the ϕ to this (extracted from the secondary‐electron cutoff energy—Figure 1a) yields an ionization potential of 7.5 ± 0.1 eV. Given that the bandgap for polycrystalline Sm 2 O 3 has previously reported to be in the range 5.0–5.2 eV, [ 65 ] E f must be located very close to the conduction band edge (as depicted in Figure 1c), so the native oxide is intrinsically n‐type. It is tentatively suggested that the most likely source of n ‐doping in this context is oxygen array vacancies, such that the oxide formed is Sm 2 O 3– x where x < 1.…”
Section: Resultsmentioning
confidence: 87%
“…Given the large negative Gibbs free energy of formation of Sm 2 O 3 , −1734.6 kJ mol −1 , [ 63 ] a Sm film only 0.8 nm (≈2 Sm atoms) in thickness would be expected to oxidize very quickly in ambient air. [ 60,61,64,65 ] To confirm this, before considering the special case of 0.8 nm Sm on Cu, the ϕ of an evaporated Sm film 20 nm in thickness with and without exposure to ambient air for 15 min was measured using ultraviolet photoelectron spectroscopy (UPS) and the Kelvin probe technique. For solids, the mean‐free path of photoelectrons excited with ultraviolet light is of the order of 1 nm, so provided ≥1 nm of the Sm‐film‐oxidized UPS measures the ϕ of the oxide rather than that of the underlying metal with modified surface potential.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In this work, ammonium acetate was used as a main electrolyte for Cf source electrodeposition. A previous study by Myhre et al [5] showed, through Xray photoelectron spectroscopy analysis, that the carbon is also co-deposited within the Sm thin film. Ammonium nitrate was selected as an alternative electrolyte and tested at the same condition with ammonium acetate.…”
Section: Effect Of Electrolytementioning
confidence: 98%